An optimized stator and rotor design of squirrel cage induction motor for EMU train - Hilda Luthfiyah; Okghi Adam Qowiy; Arga Iman Malakani; Dwi Handoko Arthanto; Fauzi Dwi Setiawan; Teddy Anugrah Ramanel; Gilang Mantara Putra; Syamsul Kamar; Asep Andi Suryandi (Journal of Mechatronics, Electrical Power, and Vehicular Technology, 2023)
This paper aims to objectively calculate the 480-kW squirrel cage induction motor (SCIM) design for the electric multiple unit (EMU) trains. This is done by optimizing the stator slot and rotor slot design to get efficiency and power factor targets. The stator slot design is achieved by limiting the width and height of the stator slot pitch according to the specified range. A depth-to-width ratio is used according to the range to optimize the design of the rotor bar slot. The design process of the induction motor consists of three steps: it determines the specification design target, calculates the specified parameters of the induction motor, and simulates the design to obtain the most optimal motor design using ANSYS Maxwell. The simulation performance values obtained an efficiency of 92.547Â % and a power factor of 0.915. This value is obtained from the optimization of the rotor slot and has met the minimum requirements of efficiency and power factor in designing a SCIM. The design proposed in this paper can be developed and applied in the Indonesian domestic railway manufacturing industry.